2009
DOI: 10.1080/00288330909509997
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and ultrastructural organisation of the eye of the Mediterranean slipper lobster,Scyllarides latus:preliminary results

Abstract: Gross anatomical organisation and ultrastructure of day-and nighttime light-and dark-adapted eyes of the Mediterranean slipper lobster, Scyllarides latus, revealed that the retina of this crustacean reacts to different ambient light intensities with photomechanical changes, involving principally screening and reflecting pigments and that a circadian component controls full darkadaptation. Although similarities to the earlier investigated eyes of spiny and rock lobsters exist, one significant difference concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…These factors appear to explain the increased abundance of slipper lobsters in "Farol do Boi" relative to open areas where the soft substrate supplies no shelter. Previous studies have reported that similar rocky outcrops are preferred by S. latus in the Azores and Mediterranean Sea (Spanier et al, 1988;Martins, 1985;Spanier and e Almog-Shtayer, 1992;Barshaw and Spanier, 1994;Spanier and Lavalli, 1998;Lavalli and Spanier, 2001;Lau et al, 2009), S. astori in the Galapagos islands (Hearn, 2006), S. aequinoctialis and S. nodifer in Florida (Sharp et al, 2007) and S. squammosus and S. haanii in Hawaii (Dinardo and Moffitt, 2007). …”
Section: Discussionmentioning
confidence: 94%
“…These factors appear to explain the increased abundance of slipper lobsters in "Farol do Boi" relative to open areas where the soft substrate supplies no shelter. Previous studies have reported that similar rocky outcrops are preferred by S. latus in the Azores and Mediterranean Sea (Spanier et al, 1988;Martins, 1985;Spanier and e Almog-Shtayer, 1992;Barshaw and Spanier, 1994;Spanier and Lavalli, 1998;Lavalli and Spanier, 2001;Lau et al, 2009), S. astori in the Galapagos islands (Hearn, 2006), S. aequinoctialis and S. nodifer in Florida (Sharp et al, 2007) and S. squammosus and S. haanii in Hawaii (Dinardo and Moffitt, 2007). …”
Section: Discussionmentioning
confidence: 94%
“…While both Panulirus and Jasus species have been investigated in palinurids, thus far only one study has been undertaken on the eye structure of scyllarids (Scyllarides sp.). Like the palinurid eye, the scyllarid eye consists of numerous ommatidia separated from the retinular cells by a clear zone that is composed of cytoplasmic extensions from the proximal end of the cone cells as well as shielding pigment cells (Lau et al, 2009). There are eight retinula cells per ommatidium, seven of which contribute to a central rhabdom that is spindle-shaped.…”
Section: Photoreceptorsmentioning
confidence: 99%
“…The eighth cell contributes only in a minor way to the rhabdom. Axons emerging from the retinular cells are bundled into clusters (Lau et al, 2009). Compared with Jasus spp., Scyllarides spp.…”
Section: Photoreceptorsmentioning
confidence: 99%
See 2 more Smart Citations